Boosting Biomass Quantity and Quality by Improved Mixotrophic Culture of the Diatom Phaeodactylum tricornutum - Villanova, Valeria; Singh, Dipali; Pagliardini, Julien; Fell, David; Le Monnier, Adeline; Finazzi, Giovanni; Poolman, Mark (Frontiers in Plant Science, 2021)
Diatoms are photoautotrophic unicellular algae and are among the most abundant, adaptable and diverse marine phytoplankton. They are extremely interesting not only for their ecological role but also as potential feedstocks for sustainable biofuels and high-value commodities such as omega fatty acids, because of their capacity to accumulate lipids. However, the cultivation of microalgae on an industrial scale requires higher cell densities and lipid accumulation than those found in nature to make the process economically viable. One of the known ways to induce lipid accumulation in Phaeodactylum tricornutum is nitrogen deprivation which, comes at the expense of growth inhibition and lower cell density. Thus, alternative ways need to be explored to enhance the lipid production as well as biomass density to make them sustainable at industrial scale. In this study, we have used experimental and metabolic modelling approaches to optimise the media composition, in terms of elemental composition, organic and inorganic carbon sources and light intensity, that boost both biomass quality and quantity of P. tricornutum. Eventually, the optimised conditions were scaled-up to 2L-photobioreactors, where a better system control (temperature, pH, light, aeration/mixing) allowed a further improvement of the biomass capacity of P. tricornutum to 12 g/L.